CHALLENGES OF INCREASING COMPETETIVENESS OF SERBIAN AGRO-INDUSTRY IN THE PROCESS OF MITIGATION OF EMERGENCY SITUATION - Domazet, Siniša; Radović, Vesela; Cvijanović, Drago (Economics of Agriculture, 2016)
Protection of agro-industry in emergency situations is of vital importance for economic and social development of a country. This paper is therefore created with a view of assessing the degree of resilience of economic entities within agro-industrial sector in the Autonomous Province (AP) of Vojvodina and partially in the Republic of Serbia in emergency situations, so that measures to increase their competitiveness could be undertaken. The methods adequate for social sciences were used: positive law method, logical induction and deduction, multidisciplinary approach, as well as statistical method. The research established that the economic entities mainly have their own fre rescue and procedure plans, but not emergency action plans. Special fnancial assets have not been allocated for that purpose either. Businessmen are not acquainted with the existence of ISO 22301:2012 standard, which may be exceptionally useful in solving this problem. The degree of resilience of economic entities in the AP of Vojvodina in emergency situations is 64.2%. It is necessary in the forthcoming period to improve the implementation of regulations, particularly in the feld of emergency action plans, but also the possibilities to implement ISO 22301:2012 standard.